2014
DOI: 10.1007/s00216-014-8002-6
|View full text |Cite
|
Sign up to set email alerts
|

NMR-based metabolomics study of the biochemical relationship between sugarcane callus tissues and their respective nutrient culture media

Abstract: The culture of sugarcane leaf explant onto culture induction medium triggers the stimulation of cell metabolism into both embryogenic and non-embryogenic callus tissues. Previous analyses demonstrated that embryogenic and nonembryogenic callus tissues have distinct metabolic profiles. This study is the follow-up to understand the biochemical relationship between the nutrient media and callus tissues using one-dimensional (1D 1H) and two-dimensional (2D 1H–13C) NMR spectroscopy followed by principal component a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…The 1D 1 H NMR metabolomics profile analysis along with the biochemical pathway analysis was performed to elucidate the metabolite differences between CA and the CL watermelon cultivars. In addition to the 1D 1 H NMR, 2D 1 H-13 C HSQC spectra was also performed to verify the 1 H assignments (Mahmud et al, 2014). The metabolic differences in this study between CA and CL could be the result of years of evolution between these two Citrullus spp.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The 1D 1 H NMR metabolomics profile analysis along with the biochemical pathway analysis was performed to elucidate the metabolite differences between CA and the CL watermelon cultivars. In addition to the 1D 1 H NMR, 2D 1 H-13 C HSQC spectra was also performed to verify the 1 H assignments (Mahmud et al, 2014). The metabolic differences in this study between CA and CL could be the result of years of evolution between these two Citrullus spp.…”
Section: Discussionmentioning
confidence: 82%
“…Buckets with corresponding p values <0.05 were considered statistically significant. Lastly, the metabolites corresponding to the peaks in the buckets were identified using the Biological Magnetic Resonance Data Bank (BMRB) (www.bmrb.wisc.edu/ metabolomics/), Madison Metabolomics Consortium Database (MMCD) (http://mmcd.nmrfam.wisc.edu/), ChenomX NMR Suite (ChenomX Inc., Edmonton, AB, Canada), and published studies (Mahmud et al, 2014). Metabolic data interpretation was facilitated with the Metabolic Pathway Analysis (MetPA) component of MetaboAnalyst3.0 (Xia and Wishart, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Glucose and fructose concentrations have been shown to vary greatly during the developmental stages and their concentrations considerably declined by the later stages of embryo maturation in black and white spruce Iraqi and Tremblay (2001). Also, sucrose concentration was significantly higher in embryogenic callus than in non-embryogenic callus of sugarcane plants (Mahmud et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Anand et al (2011) also reported the various bioactive chemical compounds by NMR spectral analysis in Zehneria scabra. The results showed that the usage of 1D 1 H NMR for comparing metabolic profiles of in vitro culture samples can be useful for understanding the biochemical relationships (Mahmud et al, 2014).…”
Section: Metabolomic Analysis By 1d 1 H-nmrmentioning
confidence: 99%